Zróżnicowanie sezonowe składu pokarmu sarny europejskiej na terenie Żytomierskiego Polesia Ukrainy - Krasnov, Volodymyr; Boiko, Sergii; Gulik, Igor; Shelest, Zoia; Sieniawski, Waldemar (Leśne Prace Badawcze, 2026)
The botanical composition of the European roe deer diet in the radioactively contaminated forest ecosystems of Zhytomirske Polesie of the Ukraine was investigated. Deer were caught monthly over a two–year period on three plots in forest habitats typical for Zhytomirske Polesie (fresh and moist mixed coniferous forests and mixed broadleaved forests). An analysis of the stomach contents of hunted deer showed that they consumed leafy as well as leafless stems, grasses, fruits and mushrooms depending on the season and availability of forest plants. Each season was characterized by one major dietary component. In the spring, the main component of the deer diet was the stems of woody plants. 44 species of vascular plants (3% of the natural flora of the region) were identified in the roe deer diet including 41 species of Magnoliophyta , of which 34 species of Magnoliopsida and 7 species of Liliopsida, 2 species of Polipodiophyta and one species of Pinophyta . Species such as aspen ( Populus tremula ), oak ( Quercus robur ), blackberry ( Rubus nessensis ) and bilberry ( Vaccinium myrtillus ) were consumed year-round.